Enlisting Manuscripts and Ancient Texts Related to Ayurveda Available in Nepal - Tamrakar, Abhishek; Upadhyaya, Vasudev; Kumar Thakur, Santosh (International Research Journal of Ayurveda & Yoga, 2025)
Introduction: Manuscripts are handwritten documents that preserve the rich heritage of the country. Nepal has a rich collection of manuscripts in both public and private collections. They are mainly stored in the National Archive, Kaiser Library, and Asa Library and have been digitized with the help of the German government. The manuscripts related to Ayurveda have hardly been explored, with only a few manuscripts edited and published. This research work enlists the manuscripts stored in Nepal and makes an attempt to group them into various branches of Ayurveda. Methods: The details of the manuscripts available in Nepal in the National Archive, Government of Nepal, various libraries and in personal possessions were recorded according to the manuscript detail form of the National Mission for Manuscripts, Government of India. Result and Conclusion: They were then analyzed based on language, script, materials, and subject or branches of Ayurveda. During the study, a total of 2324 manuscripts were studied and they were written in seven different languages, eleven different scripts, in eight different materials and were related to eighteen different branches of subjects of Ayurveda. These manuscripts need to be explored to enhance our understanding of Ayurveda.